Alkaline biodegradable implants for osteoporotic bone defects—importance of microenvironment pH. Issue 1 (January 2016) - Liu, W.; Wang, T.; Yang, C.; Darvell, B.; Wu, J.; Lin, K.; Chang, J.; Pan, H.; Lu, W.
Abstract Summary Change of microenvironment pH by biodegradable implants may ameliorate unbalanced osteoporotic bone remodeling. The present work demonstrated that a weak alkaline condition stimulated osteoblasts differentiation while suppressed osteoclast generation. In vivo, implants with an alkaline microenvironment pH (monitored by a pH microelectrode) exhibited a promising healing effect for the repair of osteoporotic bone defects. Introduction Under osteoporotic conditions, the response of the bone microenvironment to an endosseous implant is significantly impaired, and this substantially increases the risk of fracture, non-union and aseptic implant loosening. Acid-base equilibrium is an important factor influencing bone cell behaviour. The present purpose was to study the effect of a series of alkaline biodegradable implant materials on regeneration of osteoporotic bone defect, monitoring the microenvironment pH (μe-pH) over time. Methods The proliferation and differentiation potential of osteoporotic rat bone marrow stromal cells and RAW 264.7 cells were examined under various pH conditions. Ovariectomized rat bone defects were filled with specific biodegradable materials, and μe-pH was measured by pH microelectrode. New osteoid and tartrate-resistant acid phosphatase-positive osteoclast-like cells were examined by Goldner's trichrome and TRAP staining, respectively. The intermediate layer between implants and new bone were studied using energy-dispersive X-ray spectroscopy (EDX) linear scanning. Results In vitro, weak alkaline conditions stimulated osteoporotic rat bone marrow stromal cells (oBMSC) differentiation, while inhibiting the formation of osteoclasts. In vivo, μe-pH differs from that of the homogeneous peripheral blood and exhibits variations over time particular to each material. Higher initial μe-pH was associated with more new bone formation, late response of TRAP-positive osteoclast-like cells and the development of an intermediate 'apatitic' layer in vivo. EDX suggested that residual material may influence μe-pH even 9 weeks post-surgery. Conclusion The pH microelectrode is suitable for in vivo μe-pH detection. Alkaline biodegradable materials generate an in vivo microenvironmental pH which is higher than the normal physiological value and show promising healing effects in the context of osteoporotic bone defects.